POLA MAKAN PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS RAWAT JALAN DI RSUD dr. PIRNGADI MEDAN TAHUN 2009 - Siagian, Albiner; Situmorang, Eva Yanti; Aritonang, Evawany Y. (Jurnal Pangan Gizi dan Kesehatan, 2010)
Obesity, diabetes mellitus, and hypertension in patient with renal kidney disorder increase the risk of renal failure which is characterized by decrease in the filtration capacity of kidney (glomerulus filtration pace). If the filtration capacity below 15 cc per minute, patient should had take hemodialysis for survival. In addition, it is important for them to control their eating pattern. The objective of the study would be to know food consumption pattern of patient with kidney failure taking ambulatory hemodialysis. This is a descriptive study with a cross-sectional design. Population was patient with renal failure undergoing ambulatory hemodialysis in RSUD dr. Pirngadi Medan. The size of sample was 55 of patients taken purposively. The data of food consumption pattern were collected by means of food frequency questionnaire and 24 hours food recall which was conducted two times. The result showed that most of the patients aged between 54 and 62 years old. Food consumption patterns─type, quantity, and frequency─were categorized as ‘not good’. Also, potassium and sodium intakes were in the ‘not good’ category. In general, the daily water intake of the patient was in excessive amount.